Uji Efektivitas Perasan Kulit Buah Naga Merah (Hylocereus polyrhizus) dan Jeruk Nipis (Citrus aurantifolia) untuk Mendeteksi Formalin pada Ikan Bandeng (Chanos chanos) - Nadia Mira Kusumaningtyas; Baiq Ema Chaeratul Mar’ah; Choirul Umi Haniyah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Milkfish is one of the foods that are rich in protein, making it easy to rot and often preserved. One of the food preservatives used is formalin. Preservation using formalin is not recommended because it can cause damage to the liver and heart. So that in this study an attempt was made to determine the levels of formalin in milkfish so that people do not consume formalin milkfish which is detrimental to their health. Red dragon fruit skin has anthocyanin content which can be used to detect formaldehyde, because anthocyanin will easily react if it is mixed with strong acid so that when it binds with acid, the color of the juice of the dragon fruit skin will become thicker. In this study, the addition of Lime was added because Lime was used as a supporting work for the skin of red dragon fruit. This study was an experiment with 6 treatments and 2 replications. The treatments were (1) dragon fruit skin juice, left for 1 minute (2) dragon fruit skin juice, left for 3 minutes (3) dragon fruit skin juice, left for 5 minutes (4) squeezing dragon fruit skin and lime juice , left for 1 minute (5) squeezing dragon fruit skin and lime juice, left for 3 minutes (6) squeezing dragon fruit skin and lime juice, left for 5 minutes. Color separation in the solution is then recorded as data. The results showed that formalin examination on milkfish using only dragon fruit skin juice gave the results of the formation of complete color separation in the solution at minute 1 (treatment 1). While formalin examination on milkfish uses a combination of squeezing dragon fruit skin and lime giving the results of the formation of color separations and deposits in the solution completely in the 3rd minute (treatment 5). This can illustrate that the juice of dragon fruit skin and a combination of squeezed dragon fruit and lemon juice can be used to detect formalin content in milkfish. The use of dragon fruit skin juice is more effective than a combination of squeezing dragon fruit and lime skin.